Implementasi Underwriting Produk Asuransi Jiwa At – Ta’min Fadhillah Dalam Meminimalisir Resiko (Studi Pada PT Asuransi Jiwa Syariah Al Amin Kediri) - Danisa, Nanda Rahma; Sulistyowati, Sulistyowati (WADIAH, 2025)
PT Asuransi Jiwa Syariah Al Amin Kediri is a life insurance company that manages the risks of each participant who joins it. The company's superior product, At Ta'min Fadhillah, provides benefits for insurance participants so that it has many enthusiasts. The At Ta'min Fadhillah product provides coverage when the participant is destined to die and provides additional benefits, namely badal hajj/umrah. Participants who join this insurance product must go through an underwriting process. Underwriting is the process of selecting prospective participants before they are declared accepted or not as insurance participants. This research uses a qualitative approach with data sources obtained from primary and secondary data. Data collection was carried out using observation, interviews and documentation methods. The data analysis process is carried out by data reduction, data presentation and data verification. The results of the research explain that the implementation of risk management in the At Ta'min Fadhillah product is by providing an age limit when participants join, giving extra premiums to participants who have high risks and exceed the predetermined provisions, and revoke the policies of participants who are late in paying premiums to prevent fraud by unscrupulous individuals. The implementation of risk management in the product underwriting process of At Ta'min Fadhillah PT Asuransi Jiwa Syariah Al Amin is carried out by identifying participants by looking at age, risk analysis of participants, risk evaluation, risk treatment and risk monitoring.